2021
DOI: 10.1007/s10098-021-02042-x
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic assessment of microalgae cultivation in a tubular photobioreactor for food in a humid continental climate

Abstract: Fish as the primary source for the essential n − 3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) cannot cover the global demand for these important nutrients resulting in a supply gap of currently 1.1 million tons of EPA + DHA annually. A further exploitation of natural fish stocks is linked to great damage to ecosystems. Oleaginous microalgae are a natural source for EPA and DHA and could possibly contribute to closing this gap. The cultivation in photobioreactors (PBR) in a ‘cold-wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Since phenolic compounds can be obtained in similar or higher amounts from readily available and inexpensive waste, developing a microalgal process for phenolics production should also target to other products in the context of a biorefinery. Under this scope, phenolics and other bioactive compounds from microalgae can be an excellent co-product of aquaculture feed, as has been recently suggested by techno-economic analysis [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since phenolic compounds can be obtained in similar or higher amounts from readily available and inexpensive waste, developing a microalgal process for phenolics production should also target to other products in the context of a biorefinery. Under this scope, phenolics and other bioactive compounds from microalgae can be an excellent co-product of aquaculture feed, as has been recently suggested by techno-economic analysis [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…WHO and other health organizations in various countries/regions recommend a dietary intake of EPA and DHA at a range of 250 to 1000 mg/day [113] and the most commonly recommended dose is 500 mg/day [9]. Fish, as the primary source of EPA and DHA, cannot meet the global demand, resulting in a gap of nearly 1.1 million tons annually [152]. A further exploitation of natural fish and other marine sources for EPA and DHA is linked to the damage of ecosystems.…”
Section: Food Applications Of Microalgae-derived N-3 Pufamentioning
confidence: 99%
“…A recent study assessed the economic potential of microalgae as food ingredients, based on a photobiorector system for the cultivation of Nannochloropsis sp. at the industrial scale in Central Germany over a time span of 30 years [152]. The cultivation in photobioreactors in a cold-weather climate showed that microalgae compared favorably to fish aquiculture.…”
Section: Techno-economic Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the economics of autotrophic cultivation of microalgae (Nannochloropsis sp.) in a photobioreactor (PBR) for food production was reported by Schade et al (2021). The production of microalgae in PBRs was chosen over open raceway ponds due to the decreased risks of contamination and higher environmental control in suboptimal climates.…”
Section: Economics Of Microalgae-and Filamentous Fungi-based Foodsmentioning
confidence: 99%